Akulturasi Kolonial dan Sunda pada Rumah K.A.R Bosscha - Sarihati, Titihan; Prastiwi, Fasya; Febrina, Naura Wafa; Arvina, Aliyya Meirissa (Program Studi Desain Interior Unikom, 2023)
This study aims to determine the acculturation of Sundanese and colonial culture taken from the results of documentation and analysis of concepts applied to the K.A.R Bosscha House. Rumah K.A.R Bosscha is a cultural heritage site in the Bandung Regency area, precisely located in Pangalengan District, in the Malabar tea plantation area. The condition of K.A.R Bosscha's house is currently functioning as a villa and museum that can be visited by the public. Until now, the building has not been researched in terms of architecture or interior. Therefore, research is needed with research limitations starting from the concept of architecture in general, the concept of interior elements (floors, walls, and ceilings), the concept of space organization, the concept of furniture, the concept of lighting, to the concept of air. This research was conducted using descriptive qualitative methods by conducting field surveys at the location of Rumah K.A.R Bosscha, conducting interviews with the person in charge and coordinator of the agrotourism unit PTPN VIII Malabar, and references from journals and books as literature studies. The results of the analysis show that K.A.R Bosscha House has the application of Sundanese and colonial cultural acculturation in the form of architectural and interior concepts. Thus, the results of this analysis can be used as a form of contribution to preserve the cultural heritage of the archipelago and colonials in Indonesian cultural heritage buildings.